Is there any relationship between healthcare professionals' OCB and acceptance of new clinical IT? - Esmaeilzadeh, Pouyan; Sambasivan, Murali; Kumar, Naresh; Nezakati, Hossein * (2010)
Although compared to other industries the utilization of IT has slowly increased in many healthcare organizations, a variety of IT systems in the forms of clinical information systems, personal digital assistants, electronic patient records and other applications have gradually become established in the healthcare industry. Information technology has been enhanced as a means to advance patient care and outcomes. Yet, it is impractical to imagine that if a new clinical information system is adopted by a healthcare organization all organizational members will be willing to utilize the system simply. As healthcare professionals play an important role in the healthcare industry, there is no doubt that introducing new medical IT should be coupled with healthcare professionals’ acceptance to use the IT properly. Clinical IT applications in healthcare are regarded as a key element in raising the quality of medical care. However, factors affecting the healthcare professionals’ adoption behavior regarding the clinical IT systems are still not completely clear. By integrating the professional